Near-universal same-day linkage to ART care among newly diagnosed adults living with HIV: A cross-sectional study from primary health facilities, in urban Malawi. - Rachel Chihana; Chaplain Katumbi; Sufia Dadabhai; Agness Kaumba; Atusaye Mughogho; Victor Singano; Victor Mwapasa; Ken Malisita (Public Library of Science (PLoS), 2023)
Malawi HIV treatment guidelines recommend same-day antiretroviral therapy (ART) initiation. Overall 97.9% of Malawians living with HIV (PLHIV) are on ART, same-day ART initiation prevalence and factors that facilitate it have not been fully described. We assessed same-day ART initiation and described individual, health system and health facility infrastructural factors at health facilities supported by expert clients (EC). ECs are lay PLHIV who support other PLHIV. The study was conducted in urban and semi-urban primary health facilities, in Blantyre, Malawi. It was a cross-sectional, descriptive survey of PLHIV and health facility leaders. Eligibility criteria included age ≥ 18 years, new diagnosis of HIV, received counselling from ECs, and offered same-day ART. The study was conducted from December 2018 to June 2021, and 321 study participants enrolled. Mean age (standard deviation) was 33 years (10) with 59% females. In total, 315 (98.1%) initiated same-day ART. Four participants did not because of mental unpreparedness, one wanted to try herbal medicine and one was concerned about stigma related to taking ART. Participants reported health facility accessibility (99%, 318/321), privacy (91%, 292/321) and quality of counselling by EC as excellent (40%, 128/321). Same-day ART was nearly universal. Participants' satisfaction with health services delivery, the presence of EC, and infrastructural characteristics such as adequate privacy were cited as reasons favoring same-day linkage to ART. The most cited reason for not starting same-day ART was mental unpreparedness.